Prevalence and Diagnostic Test Comparison of Brucellosis in Cattle in Pabna and Mymensingh Districts of Bangladesh: Brucellosis Prevalence in Cattle - Rahman, Md. Siddiqur; Azad, Md. Khairul; Ahasan, Md. Shamim; Ahasan, Md. Shamim; Sarker, Roma Rani; Chakrabartty, Amitavo; Jasim Uddin, Mohammad; Akter, Laila (Biological Sciences - PJSIR, 2013)